THE INTEGRATION OF GENDER INTO THE TEACHING OF CLASSICAL SOCIAL THEORY: HELP FROM THE HANDMAID'S TALE* - Gotch-Thomson, Susan (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
One of the thorniest issues facing the classroom instructor is the integration of gender, race, and class into the curriculum.